Triple-play (un)bundled pricing – cui bono? - Bronwyn E. Howell; Petrus H. Potgieter (International Telecommunications Society (ITS), 2017)
Bundling of broadband access with other services has been a defining characteristic of internet access markets for as long as broadband technologies have been available. Initially, cable television competitors entered telecommunications markets by bundling first voice telephony and subsequently (broadband) internet access with their television products. The fear that bundling broadband access with live sport content could distort competition in broadband markets by first facilitating the assumption of a dominant position in broadband markets and then the squeezing-out of small rivals with low levels of investment but higher costs led to the New Zealand Commerce Commission recently declining to grant clearance for a merger between the dominant pay television provider and the number two (by market share) fixed line broadband provider also the number one mobile operator (Commission 2017; B. E. Howell and Potgieter 2017a; B. E. Howell and Potgieter 2017b). We investigate the situation where a basic content package, a premium content package and broadband are offered by a firm and analyse the firm's price-setting behaviour when customers react to a given set of prices by maximizing their individual consumer surplus. Numerical simulations with random customer valuations is used to illustrate the multiplicity of outcomes that can be expected from a regulatory intervention. We discuss issues arising from this analysis that should be pertinent to decisions in similar cases.
Keywords: 330